Capital and its Importance to Economists. (College of Basic Education Research Journal, 2025)
Capital Plays important role in important issues enlisted within specific additions and principles  like - increasing and doubling productivity. You can start your own business without having  capital for it, and this is necessary if you choose to increase your productivity and   obtain multiple products that you provide. Capital’s role became larger and more important, specially within great advances in technology  . Goods that can be produced manually over a long period are now produced many times more in a short period through  use of specialized equipment and machines. Capital provides equipment and raw materials for manufacturing. Capital With aim of providing necessary raw materials  for production in good quality and sufficient quantity, it also provides  necessary equipment and devices that facilitate  production process, without which it would be impossible to improve and increase productivity.
Keywords: Capital; Economists; Raw Materials; Good Production; Increased Productivity.